Normal saline versus a balanced crystalloid for goal-directed perioperative fluid therapy in major abdominal surgery: a double-blind randomised controlled study. (February 2018) - Pfortmueller, C.A.; Funk, G.-C.; Reiterer, C.; Schrott, A.; Zotti, O.; Kabon, B.; Fleischmann, E.; Lindner, G.
Abstract: Background: This double-blind randomised controlled trial investigated whether normal saline or a balanced crystalloid has distinct effects on vasopressor use in patients undergoing major abdominal surgery. Methods: Patients received either normal saline 0.9% or an acetate-buffered crystalloid for intraoperative volume replacement in a goal-directed fashion. The primary outcome was need for vasopressors; the secondary outcomes were the total dose of catecholamines, total perioperative fluid, and unplanned intensive care admissions. Results: This study was terminated early for safety reasons. A total of 60 out of the planned 240 patients were randomized. Thirty patients received normal saline and 30 patients received the balanced crystalloid, with a total volume of 3427 (2732–4130) ml and 3144 (1673–4926), respectively. The normal-saline group developed hyperchloraemic metabolic acidosis. More patients needed vasopressors for circulatory support in the normal-saline group compared with the buffered crystalloid group (97% vs 67%, respectively; P =0.033). The median weight and anaesthesia duration-adjusted dose of norepinephrine were 0.11 (0.00–0.45) ng kg −1  min −1 and 0.00 (0.00–0.00) kg −1  min −1 in the normal-saline and balanced-crystalloid groups, respectively ( P =0.003). Cox regression revealed that the need for vasopressors was related to a high volume of administered fluid, normal-saline resuscitation, and lower mean arterial blood pressure. There was no difference between the groups in total perioperative fluid and unplanned intensive-care-unit admissions. Between-group differences in the duration of anaesthesia did not influence the necessity for a vasopressor. Conclusions: Compared with patients receiving a balanced crystalloid, normal saline in patients undergoing major abdominal surgery was associated with an increased need for vasopressor support. This should be interpreted in view of the large volume of fluid resuscitation and the small sample size because of the preliminary termination of the study. Clinical trial registration: EudraCT 2014-004867-19, NCT 02414555.